Forecasting Berbasis Statistik Dalam Manajemen Investasi Organisasi Nirlaba: Studi Pada PKK Perumahan di Sidoarjo - Rizky, Fasha Umh (Tanzhim: Jurnal Dakwah Terprogram, 2025)
Non-profit organizations need to make investments as a way to increase capital for growth or maintain capital value against inflation. However, for leaders to decide on the appropriate investment instruments, several considerations are needed, one of which is predicting the returns on the targeted investment instruments. The leadership of the PKK Housing Cooperative at Sapphire Residence Block 6 Prasung, Buduran, Sidoarjo plans to invest a portion of its cash reserves in a savings and loan cooperative. However, to decide whether to proceed with the investment, the leadership requires a prediction of the potential returns that could be achieved by investing in the savings and loan cooperative. This quantitative study aims to generate a profit forecast for the PKK of Sapphire Residence Block 6 Prasung, Buduran, Sidoarjo. Data was obtained through interviews with the management and a review of the credit union's cash flow reports. Forecasting analysis was conducted using multiple regression analysis. The study results indicate that the data meets the classical assumption tests and can be used with multiple regression analysis to predict the potential profits that the Management Committee could achieve by investing in the Credit Union. With the formula Y=27,682 X1 + 17,255 X2, it was found that the potential profit for the PKK is Rp 27,682 per account opened at the Credit Union, or 5.54%. Based on this finding, the recommendation is that PKK leaders can invest PKK funds in the Savings and Loan Cooperative because there is no potential for loss and they can earn a 5.54% profit by opening one account.